Legal issues relating to new ventures: protecting your intellectual assets - Sherman, Andrew (Henry Stewart Talks, 2011)
Intellectual & human capital, Intangible assets & intellectual property types, Intellectual Asset Management (IAM), Intellectual property law, Patents: key issues, Trademarks: key issues, Copyrights: key issues, Work for hire, Trade secrets: key issues, Standards for protection -Implementing a protection program, Trade secret litigation, Trade dress: key issues, Harvesting process, Intellectual assets, growth and revenues